PERENCANAAN STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 3 BANGKAL KECAMATAN SERUYAN RAYA KABUPATEN SERUYAN - Hayatunufus Hayatunufus; Siminto Siminto (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The purpose of this study is to analyze the planning of school principals in improving teacher performance at SDN 3 Bangkal, Seruyan Raya District, Seruyan Regency. The research method used is qualitative. Data collection techniques are carried out by interviews, observation and documentation. Data collection techniques with interviews, observation and documentation. Data analysis techniques used 1) data reduction (data reduction), 2) data presentation (data displays and 3) conclusion drawing/verification. The results of this study are: planning for school principals in improving teacher performance at SDN 3 Bangkal, Seruyan Raya District, Seruyan Regency, teacher performance in accordance with their duties and responsibilities, this can be seen before the teacher carries out the learning process in class, the teacher makes lesson plans and prepares tools , so that they are able to create a good learning situation. When there are problems with students, the teacher who becomes the home visit homeroom teacher in order to understand the situation at the student's home. Planning the principal's strategy in improving teacher performance includes: 1), Teacher Performance Development in lesson planning so that teachers can make lesson plans with optimal results. 2) MGMP, school principals encourage teachers to be active in the MGMP forum and utilize this knowledge- sharing forum to achieve increased teacher performance in schools, especially in preparing lesson plans (RPP) so that no more teachers are found whose learning designs are adopted from other people's RPPs. 3) Involve teachers in training (Education and Training) to improve teachers' abilities so that their learning becomes better by involving teachers in training.